A string oscillations simulation with boundary conditions of hysteresis type. (2nd September 2018) - Kamenskii, Mikhail; Wen, Ching-Feng; Zvereva, Margarita
Abstract: In the present paper we investigate the initial – boundary value problems describing oscillation processes with boundary conditions of hysteresis type. Analogues of the d'Alembert formula are obtained. Some control problems are analysed and explicit forms of control functions are presented.